2023
DOI: 10.1186/s41235-023-00484-z
|View full text |Cite|
|
Sign up to set email alerts
|

Warning signals only support the first action in a sequence

Abstract: Acting upon target stimuli from the environment becomes faster when the targets are preceded by a warning (alerting) cue. Accordingly, alerting is often used to support action in safety-critical contexts (e.g., honking to alert others of a traffic situation). Crucially, however, the benefits of alerting for action have been established using laboratory tasks assessing only simple choice reactions. Real-world actions are considerably more complex and mainly consist of sensorimotor sequences of several sub-actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…We found that the mean pupil size was larger with a preceding visual alerting cue, t(209) = − 7.071, p < .001, d z = − 0.488, BF 10 = 3.2 × 10 8 , and an auditory alerting cue, t(209) = − 8.706, p < .001, d z = − 0.601, BF 10 = 5.9 × 10 12 , compared with the no cue condition (cf. Dietze et al, 2023;Petersen et al, 2017). On average pupil responses from baseline for the interval from 1500 ms to 1600 ms relative to cue onset were 0.053 mm (SD = 0.123 mm) following the visual alerting cue and 0.052 mm (SD = 0.115 mm) following the auditory alerting cue.…”
Section: Pupillary Resultsmentioning
confidence: 94%
“…We found that the mean pupil size was larger with a preceding visual alerting cue, t(209) = − 7.071, p < .001, d z = − 0.488, BF 10 = 3.2 × 10 8 , and an auditory alerting cue, t(209) = − 8.706, p < .001, d z = − 0.601, BF 10 = 5.9 × 10 12 , compared with the no cue condition (cf. Dietze et al, 2023;Petersen et al, 2017). On average pupil responses from baseline for the interval from 1500 ms to 1600 ms relative to cue onset were 0.053 mm (SD = 0.123 mm) following the visual alerting cue and 0.052 mm (SD = 0.115 mm) following the auditory alerting cue.…”
Section: Pupillary Resultsmentioning
confidence: 94%
“…Considering the overall low number of guiding fixations could hinder this absolute stability translating to the interindividual level. Because the range of the measure is restricted, the results cannot reliably differentiate between persons ( Dietze, Recker, & Poth, 2023 ; Hedge et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Warning cues facilitate sensorimotor processing (Dietze et al, 2023) and induce cardiac deceleration (Skora et al, 2022). However, the role of the increase in IBI for sensorimotor processing is not completely understood.…”
Section: Discussionmentioning
confidence: 99%